Silver-modified atraumatic restorative technique: A comprehensive review - Mohammed Mubarak Aldosari; Abdulmajeed Rasheed Alkhathlan; Osama Nasser Alasmari (Wolters Kluwer Medknow Publications, 2024)
Introduction: The Silver-modified Atraumatic Restorative Technique (SMART) is a new emerging technique and presents a compelling option for the management of carious lesions as it allows for a more conservative and efficient treatment method, ultimately leading to improved preservation of tooth structure. Aims: The aim of this review is to highlight the SMART, its appropriate indications and contraindications, and its effectiveness. Materials and Methods: A comprehensive search was conducted across several scientific databases. A total of 82 articles were gathered and subsequently subjected to screening based on predetermined inclusion criteria. A comprehensive compilation of 37 articles was utilized for the purpose of this evaluation. Results and Discussion: Based on careful case selection, it is possible to suggest the use of this treatment as a potential biologic adjunctive therapy for managing asymptomatic deep dentinal lesions in pediatric patients. The SMART is a valuable treatment modality for treating apprehensive patients and patients who cannot withstand long-duration treatment. Conclusion: The SMART approach is an efficient and reliable method for treating dental caries. It has been extensively studied and documented that the application of silver diamine fluoride (SDF) is successful in preventing the advancement of dentin caries. This makes SDF a beneficial addition to enhance the effectiveness of the atraumatic restorative treatment in primary dentition.